RESEARCHES ON THE RELATIONSHIP BETWEEN LINEAR TYPE TRAITS AND PRODUCTIVE LONGEVITY OF COWS OF UKRAINIAN BROWN DAIRY BREED - Leontii KHMELNYCHYI; Serhii KHMELNYCHYI; Victoria VECHORKA; Evgeniya SAMOKHINA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The phenotypic relations between type traits and longevity indices in cows of Ukrainian Brown dairy breed in the Sumy region of Ukraine were analyzed. Linear estimation was performed according to ICAR recommendations (2014). In this study 18 traits of type are considered. The average lifetime of cows was 6.7 years, which corresponding to an average productive use of 4.67 years. Longevity yield for cows amounted to an average of 21,517 kg of milk, or 8.8 kg per one day of life, or 13.3 kg per day of productive use. Phenotypic correlations were between final assessment and lifetime (r=0.321), longevity milk yield (r=0.398) and milk fat (r=0.369). In general, phenotypic correlations between linear traits of type and longevity traits varied from -0.192 to 0.422. Sufficient levels of correlations indicated that indirect selection on the basis of height (r=0.122-0.209), body depth (r=0.209- 0.268), angularity (r=0.318-0.422), rump width (r=0.226-362), front udder part attachment (r=0.275-0.396), rear udder part attachment (r=0.254-342), central ligament (r=0.245-371), udder depth (r=0.228-0.244) and body condition score (r=-0,192…-0,378) can lead to an effective improvement of cows longevity traits.